The impact of internal social responsibility on organisational commitment : the case of Jerónimo Martins Group - Figueiredo, Daniela da Silva (2017)
The Jerónimo Martins Group is a multinational firm operating in the Distribution and Agribusiness sectors, with a strategy focused on value creation and sustainable development. It assumes a Corporate Responsibility governed by five pillars; however, this thesis focuses essentially on the following one: “Being a Benchmark Employer”. The Group ensures benefits to the members of the organisation, such as training, development, compensation, and a positive working environment. In 2008, the company decided to go further and created a department focused on improving the quality of life of its employees. Since the company has the need to continuously guarantee that this area constitutes a differentiation factor and effectively adds value to the company, the main aim of this thesis is to investigate the relationship between employees’ perceptions of internal social responsibility and organisational commitment. Specifically, it analyse the perceptions of internal social responsibility from two different perspectives – the company and its employees – and subsequently studies the impact of seven internal dimensions on affective and normative commitment: employment stability, working environment, skills development, workplace diversity, work-life balance, tangible employee commitment, and empowerment. The analysis is based on primary and secondary research conducted with managers and employees of the Group. The main results showed that all internal dimensions are significantly and positively related to affective and normative organisational commitment.